Diseño y construcción prototipo de máquina herramienta de corte de tubería PVC para la empresa Prohuila SAS (2021)
During the execution of civil works, the company Prohuila SAS faces situations that delay the delivery period, causing economic losses in raw materials due to the incorrect cutting of pipes used in the countries. The main problem is due to human failures that at the time of cutting the pipe destroy 20% of the material. The main objective is to design a machine tool that cuts PVC pipes with precision. To meet this objective, the analysis of the problem, conceptual design, detailed design, construction, assembly and validation of the prototype were implemented, thus applying previous knowledge in resistance of materials, mechanical design and science of materials for the total construction of the prototype. Finally, it is concluded that for the design of the structure of the machine, the most appropriate material is A36 steel, since it provides resistance to static forces with a safety factor of 8. Regarding its functionality, it has a cutting disc coupled to a 2.41 hp electric motor, which works at a nominal speed of 4500 rpm and a sheer force of 8000 N. This motor is assembled to a crank restricted to one degree of freedom to ensure that no perpendicular movements are encountered. Cutting, from this it is specified that the machine reduces the loss of material to 100% as long as the measurement is done correctly.